2019
DOI: 10.1007/s12975-019-00747-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Serum Levels of Growth Factors with Good Outcome in Ischemic Stroke: a Multicenter Study

Abstract: The main objective of this research work was to study the association of serum levels of growth factors (GF) and SDF-1α with the functional outcome and reduction of lesion volume in ischemic stroke patients. In this multicenter study, 552 patients with nonlacunar stroke (male, 62.1%; mean age, 68.2 ± 11.4) were included within 24 h from symptom onset. The main outcome variable was good functional outcome (modified Rankin Scale [mRS] ≤ 2) at 12 months. Secondary outcome variable was infarct volume (in mL) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Sobrino et al explored the association between various serum biomarkers and functional outcome after ischemic stroke [ 35 ]. In this multicenter study, they included 552 patients within the first 24 h after stroke (non-lacunar etiology).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sobrino et al explored the association between various serum biomarkers and functional outcome after ischemic stroke [ 35 ]. In this multicenter study, they included 552 patients within the first 24 h after stroke (non-lacunar etiology).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies reported both the serum BDNF levels and the NIHSS during the acute stroke phase. Thirteen studies, despite measuring BDNF and scoring NIHSS, do not examine the in-between correlation [ 20 , 21 , 22 , 24 , 25 , 26 , 27 , 33 , 34 , 35 , 39 , 40 , 41 ]. Amongst the rest, nine were further meta-analyzed [ 14 , 15 , 23 , 28 , 32 , 36 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible existence of a disequilibrium state during the initial few days may also explain the conflicting results obtained with respect to the relationship between initial BDNF levels and outcomes. Wang et al found evidence for an association between BDNF and outcomes after 3 months [ 39 ], but the findings of others were negative for outcomes after 90 days [ 40 , 41 , 42 ] and 12 months [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic-ischemic brain damage (HIBD) is a common central nervous system lesion in perinatal neonates, and 25% of neonatal HIBD can develop into severe and permanent neuropsychological sequelae, including developmental delay, cerebral palsy and epilepsy, and there is still no effective therapy for the disease (Liang et al, 2010;Sobrino et al, 2020;Truttmann et al, 2020). Gene therapy for brain damage has become a popular research field, due to its potential for long-lasting and stable effects.…”
Section: Introductionmentioning
confidence: 99%